"I Smoked That Cigarette, and It Calmed Me Down": A Qualitative Analysis of Intrapersonal, Social, and Environmental Factors Influencing Decisions to Smoke Among Youth Experiencing Homelessness. Issue 2 (4th October 2021) - Patterson, Joanne G; Glasser, Allison M; Macisco, Joseph M; Hinton, Alice; Wermert, Amy; Nemeth, Julianna M
Abstract: Introduction: Approximately 70% of youth experiencing homelessness smoke cigarettes; many try to quit and are interested in formal smoking cessation programs. The purpose of this study was to describe the intrapersonal, social, and environmental contexts associated with the most recent smoking experience among youth experiencing homelessness and (2) identify differences in contextual factors by age and willingness to quit. Methods: Thirty-six youth experiencing homelessness aged 14–24 years and who reported current smoking were recruited from a drop-in center in a Midwestern city. Semi-structured in-person interviews were analyzed to understand smoking behaviors. Results: Two-thirds of participants reported stress and nicotine dependence as primary reasons for smoking, and older youth (aged 18–24 years) reported smoking to de-escalate negative emotions associated with stressful events. For 25% of participants, and especially older youth, smoking was described as part of a routine. Over 80% of participants smoked outside at the homeless drop-in center or the places they lived. Social prompts from drop-in center peers regularly preempted smoking. Younger youth (aged 14–17 years) reported smoking socially while older youth were more likely to smoke alone. Conclusions: For youth experiencing homelessness, smoking is integrated into daily life and is often used to manage stress associated with homelessness and engage socially with homeless peers. Multicomponent interventions to reduce structural stressors specific to homelessness, change social smoking norms (environmental and social context), and address stress management and nicotine dependence (intrapersonal context) are needed to support smoking cessation among youth experiencing homelessness. Implications: Youth experiencing homelessness overwhelmingly described how daily stressors associated with homelessness and nicotine dependence preceded recent smoking. Older youth (aged 18–24 years) also reported smoking as "routine", which likely underscores nicotine dependence in this group. Younger youth (aged 14–17 years) described social smoking. Researchers must develop optimized multilevel interventions to support youth experiencing homelessness who want to quit smoking. Interventions directly targeting social determinants of stress (e.g., poverty, housing instability, food insecurity) and linkages to supportive services are needed. Complementary strategies to address stress coping and nicotine dependence (intrapersonal context) and social smoking norms (social and environmental context) are also necessitated.